2001
DOI: 10.1128/iai.69.11.7146-7151.2001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Internalization and Viability of Porphyromonas gingivalis in KB Epithelial Cells by Confocal Microscopy

Abstract: Porphyromonas gingivalis (P. gingivalis) is considered to be one of the main periodontal pathogens. The goal of this work was to confirm the ability of P. gingivalis to invade host cells. We detected P. gingivalis inside KB cells by confocal microscopy and analyzed the various aspects of the adherence and internalization process. Lysates of P. gingivalis-infected KB cells were also examined using anaerobic growth techniques. The results showed the viability and ability to replicate, inside the host cells, of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
6
34
0
1
Order By: Relevance
“…1b,. This is in agreement with other published data that used KB cells (Dorn et al, 2000;Eick et al, 2006;Houalet-Jeanne et al, 2001), and similar levels of invasion have been reported using normal oral keratinocytes (Lamont et al, 1995). When the invasion levels of the recovered bacteria were analysed after a second round of invasion with fresh cells we observed an increase in the percentage of bacteria able to invade the OSCC cells for both strains of over threefold (Fig.…”
Section: Resultssupporting
confidence: 83%
“…1b,. This is in agreement with other published data that used KB cells (Dorn et al, 2000;Eick et al, 2006;Houalet-Jeanne et al, 2001), and similar levels of invasion have been reported using normal oral keratinocytes (Lamont et al, 1995). When the invasion levels of the recovered bacteria were analysed after a second round of invasion with fresh cells we observed an increase in the percentage of bacteria able to invade the OSCC cells for both strains of over threefold (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Nevertheless, HeLa cells, which were more resistant than KB cells to detachment at high concentrations of supernatant, still retained differences between their staining patterns with supernatant and HRgpA when these cells were exposed to comparable BApNA levels. Internalization of viable P. gingivalis organisms by epithelial cells in vitro has been described previously by a number of groups (1,13,23), and intracellular bacteria have been shown to release outer membrane vesicles both in monolayer cultures of KB cells (19) and in multilayered cultures of human pocket epithelium (33). Interestingly, the perinuclear localization of the viable whole organisms described in gingival epithelial cells and KB cells (1,19) resembled the nuclear targeting we observed with MAb 1A1-reactive material in W50 culture supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…Internalization of viable P. gingivalis organisms by epithelial cells in vitro has been described previously by a number of groups (1,13,23), and intracellular bacteria have been shown to release outer membrane vesicles both in monolayer cultures of KB cells (19) and in multilayered cultures of human pocket epithelium (33). Interestingly, the perinuclear localization of the viable whole organisms described in gingival epithelial cells and KB cells (1,19) resembled the nuclear targeting we observed with MAb 1A1-reactive material in W50 culture supernatant. Belton et al (1) stated that the perinuclear region of keratinocytes contains many organelles, but the functional significance of the association remained to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…43,46,47 However, in KB cells the bacteria are found free in the cytosol or within single-membrane bound vacuoles. 19,[48][49][50] P. gingivalis has been shown to promote cell death in KB cells as well as in gingival fibroblasts. 51,52 Our data suggest that P. gingivalis does not promote cell death in HCAEC (unpublished observations).…”
Section: Bacterial Persistence and Host Cell Survivalmentioning
confidence: 99%